Profitability as a Mediation for Problem Loans, Third-Party Funds, BI Rate on Company Value - Nur Latifah, Putri; Nur Aisyah, Esy (Jurnal Ecogen, 2024)
This research from 2016 to 2022 intends to understand the relationship between the Islamic banking sector in Indonesia, company value, where profitability is the mediator between non-performing loans and third-party funds, and interest rates. This methodology uses purposive sampling to produce nine samples representing Islamic financial institutions. The criteria is an annual banking report, which can be obtained on the bank's official website or at the OJK. The quantitative descriptive methodology used in this research consists of the Sobel test and panel data regression analysis. Data analysis findings show that while profitability and the BI rate impact a company's value less, non-performing loans and third-party funding do. Profitability is unaffected by BI rates, non-performing loans, and third-party funding. Profitability does not mitigate the effect of third-party financing, non-performing loans, and the BI rate on a company's value.